1978
DOI: 10.1099/00221287-106-1-27
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma (Schizotrypanum) dionisii: Influence of Mouse Peritoneal Macrophages and Calf Sera on Extracellular Growth in vitro at 37  C

Abstract: 27Macrophages and certain batches of sera were essential for extracellular multiplication of Trypanosoma dionisii in vitro in medium 199 with 20 % (v/v) calf serum at 37 "C. In mixtures of ' good ' and ' bad ' batches of sera, multiplication increased as the proportion of the former was increased. Mixtures of 'bad' and 'intermediate' sera permitted virtually no growth. Phagocytosis of parasites by macrophages was unaffected by different batches of sera, though reduced in medium 199 alone. Replacement of supern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1979
1979
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Culture forms of T. dionisii (stock P2) isolated by Dr J. R. Baker from bats (Baker, 1980) were grown in liquid medium L4 NHS at 28 °C, either for 2 days for epimastigotes or for 9 days for trypomastigotes (Baker, Liston & Selden, 1976;Baker & Selden, 1978). When radioactive trypanosomes were required [5,6-3 H] uridine (0-5 mCi/20 ml) was added to the growth medium at the beginning of the growth period (Sanderson, Bunn Moreno & Lopez, 1978).…”
Section: Trypanosoma Dionisiimentioning
confidence: 99%
“…Culture forms of T. dionisii (stock P2) isolated by Dr J. R. Baker from bats (Baker, 1980) were grown in liquid medium L4 NHS at 28 °C, either for 2 days for epimastigotes or for 9 days for trypomastigotes (Baker, Liston & Selden, 1976;Baker & Selden, 1978). When radioactive trypanosomes were required [5,6-3 H] uridine (0-5 mCi/20 ml) was added to the growth medium at the beginning of the growth period (Sanderson, Bunn Moreno & Lopez, 1978).…”
Section: Trypanosoma Dionisiimentioning
confidence: 99%
“…We show that the use of Trypanosoma dionisii, a member of the Trypanosoma genus and Schyzotrypanum subgenus, may constitute an alternative model for drug screening and further biochemical studies on the mechanism of Chagas therapy. Since the classical studies carried out by Baker and Selden [31], bloodstream trypomastigotes have been isolated from bats and shown to infect mammalian cells in vitro. They transform into amastigote forms that proliferate within the host cells and subsequently transform back in trypomastigotes that are released into the extracellular medium and infect new cells.…”
Section: Discussionmentioning
confidence: 99%
“…T. vespertilionis and T. dionisii did not develop in chicken fibroblasts, whereas amastigotes of T. hedrieki and T. myoti did. European workers found that T. dionisii developed better in mammalian macrophages than in fibroblasts (Baker et al, 1972a(Baker et al, , 1972bListon, 1975;Baker & Selden, 1978;Liston & Baker, 1978). More recent work (Baker et al, 1980) showed that cultured trypomastigotes of T. dionisii would also develop in 'buffalo lung cells'.…”
Section: Discussionmentioning
confidence: 99%